Peningkatan Fungsi Kognitif Lansia Melalui Permainan Color Ball Memory - Esri Rusminingsih (Universitas Muhammadiyah Klaten, 2026)
Cognitive decline in the elderly is a significant issue that negatively impacts their quality of life, often leading to reduced ability to perform daily activities, social isolation, and depression. Cognitive stimulation has been proven effective in slowing cognitive decline, especially when delivered through innovative and engaging approaches such as technology-based educational games. This community service program aimed to conduct cognitive function screening and provide cognitive stimulation through educational games for elderly members at Posyandu Larasati, Kajen Village, Wedi Subdistrict, Klaten Regency. The activity began with cognitive screening using the Short Portable Mental Status Questionnaire (SPMSQ), followed by an intervention utilizing a visual memory game called Color Ball Memory, in which players are challenged to remember the sequence or position of colored balls. A total of 29 elderly participants joined the program, with a mean age of 68±7.5 years; the majority were female (24 participants, 82.8%) and 5 were male (18.2%). The screening results showed an average SPMSQ score of 9, indicating normal cognitive function. This activity demonstrated that technology-based educational games are well accepted by elderly participants and have the potential to serve as an effective cognitive stimulation method.